World marketing congress. International conference series. Vol. IV / William Lazer, Eric H. Shaw, Chow-How Wee - Lazer, William [et.al] (1989)
Ethical issues and social responsabilities, cross cultural studies and comparative marketing analysis, marketing management and competitive strategies, marketing in/to LCDs and NICs, retailing and retail strategies, marketing of services, new technologies for marketing decision making, buyer behavior and consumption.